Detection of hepatitis C virus and parvovirus B19 in human plasma pools by nucleic-acid amplification techniques – Trends in results of EDQM proficiency testing studies from 2004 to 2018. (June 2021) - Taconet, Laure; Seifner, Alexandra; Baylis, Sally A.; Chudy, Michael; Kreβ, Julia; Mathys, Esther; Wirz, Maria; Buchheit, Karl-Heinz; Behr-Gross, Marie-Emmanuelle
Abstract: The European Directorate for the Quality of Medicines & HealthCare (EDQM) has run proficiency testing schemes on the detection of viral contaminants in human plasma pools by nucleic-acid amplification techniques since 1999 for hepatitis C virus and since 2004 for parvovirus B19. A retrospective analysis was performed to assess their impact and identify trends and progress in the results obtained by participating laboratories over a 15-year span, from 2004 to 2018. The results demonstrate that overall performance improved over that time, especially among the regular participants. Participation in these proficiency testing schemes is therefore recommended for all interested control laboratories. This analysis also shows that hepatitis C virus detection now seems well established compared to that of parvovirus B19, which still appears more challenging.